Lipidic strategy for improving bioavailability of nucleoside HIV reverse transcriptase inhibitor - N. S. Shastina; E. O. Baranova; L. N. Dyakova; D. V. Lonshakov; V. I. Shvets (Тонкие химические технологии, 2011)
In recent years, various approaches to the prodrug design on the basis of anti-HIV active nucleoside compounds used in the therapy are intensively investigated. In this paper, the principles of modifying this class of drugs by lipid substances allowing obtained conjugates to insert in natural lipid transport and metabolic pathways that can increase nucleoside agents bioavailability are described. Literature data associated with the research of the pronucleotide approach serving the purpose of increasing nucleoside drugs therapeutical efficacy and reducing the side effects on the organism are reviewed. Experimental data obtained by the authors in course of research of synthetic routes and properties of the new lipid-modified anti-HIV nucleosides are also presented.